Limits of Italian jurisdiction in respect of actions concerning an internationally registered design: Note to ordinance no. 13504/2023 of the Italian Court of Cassation - Benini, Caterina (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
With order no. 13504 of 2023, the Italian Court of Cassation ruled on the limits of Italian jurisdiction over actions aimed at ascertaining the invalidity of the Italian portion of an internationally registered design and the non-infringement of the German portion thereof. This contribution analyses some of the issues raised by the present case, such as the identification of the place of registration of an internationally registered design under Article 24(4) of the Brussels I bis Regulation, the relevance of the principle of territoriality for the identification of the place of the harmful event under Art. 7(2) of the Brussels I bis Regulation in relation to the infringement of a national portion of an international design, and the impact that the lack of standing of a defendant which was not part of the dispute may have on the special forum for several defendants under Article 8(1) of the Brussels I bis Regulation.
Keywords: Internationally registered design; jurisdiction; alidity of the design; violation of the design; fictitious respondents and jurisdiction over connected claims